An Exploration of the Aberrant Perceptions Experienced by Westerners in the Peruvian Amazon Amid Shipibo Ayahuasca Practices. (28th March 2022) - Dudek, Agnes
ABSTRACT: Ayahuasca has become a subject of great interest in recent years. Academics, spiritual seekers, communities, and curious individuals have all been intrigued by this topic through either writing about it or direct participation in the contemporary spiritual phenomenon that is ayahuasca, which holds promises of bestowing upon its users profound wisdom or healing. However, what anthropological (but also popular) writings barely comment on are the deviant perceptions that arise out of experiences seeking amelioration or transcendence, and the subjective ways in which those experiences are interpreted. Consequently, I wish to supplement this scope of representation. In this text, I present fieldwork conducted in the Peruvian Amazon amid the Shipibo, focusing on the experiences of the spiritual seekers who came to them in search of healing or self‐discovery. I discovered a unique contradiction—participation in Shipibo ayahuasca practices while simultaneously having or developing a negative perception or attitude towards it. These aberrances are held, as I argue herein, (incognizantly) in the expressed attitudes of the Westerners (especially North American and European) as a result of the positivist notions that emerged from the Age of Enlightenment (but are not limited to it). My priority in this article is to present and expound on these atypical associations and place them against a historical (Western) background to elucidate the origin of the thus found and experienced perceptions.